Si-coated LaF3 composite material and preparation method and application thereof
By preparing the Si@LAF3 composite material, using fluoride to modify the nano -silicon particles, the structural instability of the silicon anode due to volume expansion is solved, and the lithium storage capacity of high ratio and cycle stability is achieved.
Patent Information
- Application Number
- CN202411480892.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
Smart Images

Figure CN119361641A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrode materials and relates to a Si@LaF3 composite material and a preparation method and application thereof. Background Art
[0002] With the rapid development of the economy, the demand for energy density of lithium-ion batteries continues to increase. The anodes currently used in mainstream commercial applications are mainly graphite, and their energy density is close to the theoretical limit, which makes it difficult to meet the urgent needs of social development. Silicon, as a material with abundant reserves in the earth's crust, has a very high theoretical capacity. When silicon is alloyed with lithium, the fully lithium product Li 15 Si4 phase will provide 3579mAh·g -1 The capacity of silicon anode is about 10 times that of graphite anode, and the silicon anode has a relatively low delithiation potential, and is widely regarded as the most promising next-generation anode.
[0003] Although silicon materials have many advantages as anodes, their commercialization is still limited by poor electrochemical performance. Silicon particles undergo a large volume expansion (~400%) during the lithiation / delithiation process, which generates huge mechanical stress inside, leading to the pulverization of active materials, the continuous formation of new electrode surfaces, and continuous side reactions with electrolytes. The solid electrolyte interface (SEI) formed on the anode surface continues to grow, ultimately leading to a continuous increase in lithium ion diffusion impedance and severe capacity decay.
[0004] In order to improve the structural stability of silicon negative electrodes, researchers have conducted extensive explorations for many years and have overcome volume expansion by designing silicon materials with unique structures, such as nanospheres, nanowires, nanotubes, and porous structures. Studies have shown that nano-sizing can alleviate the mechanical strain caused by volume expansion and maintain the structural integrity of silicon particles. At the same time, due to its large surface area, the diffusion path of lithium ions can be shortened. Another way to improve the stability of silicon negative electrodes is to form an "artificial" SEI by establishing an organic or inorganic coating on its surface. The establishment of a coating can prevent direct contact between active silicon and the electrolyte during the alloying process, reduce the occurrence of side reactions, and thus improve cycle stability.
[0005] Fluorides have been widely studied as cathode surface coating materials. Among them, lanthanum fluoride LaF3 has been shown to be a layered cathode for lithium-ion batteries (LiNi x Co y Mn z O2 (NCM-xyz), LiCoO2, LiMn2O4) surface coating materials are beneficial to reduce the occurrence of side reactions at the cathode and electrolyte interface and improve structural stability and thermal stability.
[0006] However, no studies on the effect of lanthanum fluoride on silicon anodes have been found so far. Summary of the invention
[0007] The present invention provides a Si@LaF3 composite material and a preparation method and application thereof, which can effectively solve the above problems.
[0008] The present disclosure is implemented as follows:
[0009] In a first aspect, the present disclosure provides a method for preparing a Si@LaF3 composite material, the method comprising: ball-milling nano-silicon and lanthanum fluoride powder in an inert environment to obtain the Si@LaF3 composite material, wherein the mass ratio of the lanthanum fluoride powder is 10%-30% based on the total amount of the nano-silicon and the lanthanum fluoride powder.
[0010] In some embodiments, the mass ratio of the lanthanum fluoride powder is 15%-25% based on the total amount of the nano-silicon and the lanthanum fluoride powder.
[0011] In some embodiments, the mass ratio of the lanthanum fluoride powder is 18%-22% based on the total amount of the nano-silicon and the lanthanum fluoride powder.
[0012] In some embodiments, the mass ratio of the lanthanum fluoride powder is 19%-21% based on the total amount of the nano-silicon and the lanthanum fluoride powder.
[0013] In some embodiments, the mass ratio of the lanthanum fluoride powder is 15%, 16%, 27%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, or 25%, based on the total amount of the nano-silicon and the lanthanum fluoride powder.
[0014] In some embodiments, the particle size of the nano-silicon powder is no greater than 150 nm.
[0015] In some embodiments, the particle size of the nano-silicon powder is 80-120 nm.
[0016] In some embodiments, the particle size of the nano-silicon powder is 90-110 nm.
[0017] In other embodiments, the particle size of the nano silicon powder is 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, 105 nm, 110 nm, 115 nm, or 120 nm.
[0018] In a second aspect, the present disclosure provides a Si@LaF3 composite material, wherein the Si@LaF3 composite material includes nano-silicon particles and an amorphous lanthanum fluoride coating layer on the surface of the nano-silicon particles, and the Si@LaF3 composite material also includes lanthanum fluoride particles dispersed between the nano-silicon particles.
[0019] In a third aspect, the present disclosure provides an application of a Si@LaF3 composite material in a lithium-ion battery anode material.
[0020] The use of the Si@LaF3 composite material prepared by the method described in any embodiment of the first aspect in a lithium-ion battery anode material, or the use of the Si@LaF3 composite material described in any embodiment of the second aspect in a lithium-ion battery anode material.
[0021] In some embodiments, the lithium ion battery is a half-cell or a full cell.
[0022] In some embodiments, the half-cell is a liquid half-cell or a solid half-cell.
[0023] In some embodiments, the full battery is a liquid full battery or a solid full battery.
[0024] In some embodiments, the lithium ion battery is a liquid lithium ion battery or an all-solid-state lithium ion battery.
[0025] In some embodiments, the liquid lithium ion battery is a liquid lithium ion half-cell or a liquid lithium ion full cell.
[0026] In some embodiments, the all-solid-state lithium ion battery is an all-solid-state lithium ion half-cell or an all-solid-state lithium ion full battery.
[0027] In some embodiments, the anode material includes graphite.
[0028] In some embodiments, in the anode material, the mass ratio of the Si@LaF3 composite material to graphite is 1:4-9.
[0029] In some embodiments, in the anode material, the mass ratio of the Si@LaF3 composite material to graphite is 1:4.8-6.7.
[0030] In some embodiments, in the anode material, the mass ratio of the Si@LaF3 composite material to graphite is 1:5.5-6.
[0031] In some embodiments, in the anode material, the mass ratio of the Si@LaF3 composite material to graphite is 1:5, 1:6, 1:7, 1:8, or 1:9.
[0032] In a fourth aspect, the present disclosure provides a lithium-ion battery anode material, wherein the anode material comprises a Si@LaF3 composite material and graphite.
[0033] A lithium-ion battery anode material, the anode material comprising the Si@LaF3 composite material and graphite prepared by the method described in any embodiment of the first aspect, or the Si@LaF3 composite material and graphite described in any embodiment of the second aspect.
[0034] In some embodiments, in the anode material, the mass ratio of the Si@LaF3 composite material is 10%-20%.
[0035] In some embodiments, in the anode material, the mass ratio of the Si@LaF3 composite material is 13%-17%.
[0036] In some embodiments, in the anode material, the mass ratio of the Si@LaF3 composite material is 14%-16%.
[0037] In some embodiments, in the anode material, the mass ratio of the Si@LaF3 composite material is 13%, 14%, 15%, 16%, or 17%.
[0038] The beneficial effects of the present disclosure are:
[0039] The present invention provides a method for preparing a Si@LaF3 composite material, and a low-cost Si@LaF3 nanocomposite material is prepared by a simple one-step ball milling method. Rigid LaF3 particles form a thin layer of lanthanum fluoride on the surface of nano silicon particles during high-energy ball milling, and excess LaF3 particles are dispersed in the silicon electrode.
[0040] Furthermore, when lithium ions are embedded, the lanthanum fluoride thin layer preferentially induces the nano-silicon particles to form a LiF-rich SEI layer with ionic conductivity and mechanical flexibility, reducing the occurrence of interfacial side reactions through effective passivation. At the same time, the lanthanum particles generated by the reaction of lanthanum fluoride and lithium ions can adsorb the anion groups of the electrolyte, promote the free migration of lithium ions in the silicon electrode, and enhance the reaction kinetics of the electrode. The LaF3 particles dispersed in the silicon electrode in an appropriate amount can alleviate the electrochemical sintering of nano-silicon particles and inhibit the local excessive volume expansion stress and damage of the silicon electrode. Therefore, compared with pure nano-silicon particles, this Si@LaF3 particle that is easy to scale up has both high specific capacity and cycle stability. Lithium storage capacity.
[0041] Furthermore, the Si@LaF3||LFP full cell maintains 125.1 mAh g after 200 cycles at 0.35C. -1 Specific capacity.
[0042] Furthermore, the all-solid-state lithium battery based on Si@LaF3 / graphite hybrid electrode was -1 After 100 cycles, the capacity remains at 491 mAh g -1Specific capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present disclosure and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0044] Figure 1 is a SEM image of pure nano-silicon particles.
[0045] Figure 2 is the SEM image of Si@LaF3-20 nanoparticles (200 nm).
[0046] Figure 3 , (a) is the SEM image (1 μm) of Si@LaF3-20 nanoparticles; (b) is the EDX image (under SEM) of Si@LaF3-20 nanoparticles.
[0047] Figure 4 It is Si@LaF 3- SEM and EDX images of 30 nm particles.
[0048] Figure 5 , (a) is the low-magnification TEM image of pure nano-silicon particles; (b) is the HRTEM image of pure nano-silicon particles; (c) is the diffraction pattern of pure nano-silicon particles; (d) is the HAADF pattern and EDX image of pure nano-silicon particles.
[0049] Figure 6 is the TEM image of Si@LaF3-20 nanoparticles (100 nm).
[0050] Figure 7 is the TEM image of Si@LaF3-20 nanoparticles (50 nm).
[0051] Figure 8 is the HRTEM image of Si@LaF3-20 nanoparticles.
[0052] Fig. 9 This is the EDX image of Si@LaF3-20 nanoparticles (under TEM).
[0053] Fig.10 These are the XRD patterns of the standard JCPDS cards for Si, LaF3 and Si@LaF3-20.
[0054] Fig.11This is the XRD pattern of Si@LaF3 composite materials with different lanthanum fluoride addition ratios.
[0055] Fig.12 Si 2p, F 1s, La 3d on Si@LaF3-20 electrode 5 / 2 XPS analysis chart.
[0056] Fig.13 The Si@LaF3 composites of pure nano-silicon and different lanthanum fluoride addition ratios at 0.3A·g -1 Comparison of cycling performance under different current densities.
[0057] Fig.14 This is a comparison chart of the rate performance of pure nano-silicon and Si@LaF3 composite materials with different lanthanum fluoride addition ratios at different current densities.
[0058] Fig.15 The Si@LaF3 composites with pure nano-silicon and different lanthanum fluoride addition ratios at 1A·g -1 Comparison of cycling performance under different current densities.
[0059] Fig.16 It is the GITT curve and lithium ion diffusion coefficient diagram of pure silicon and Si@LaF3-20 electrodes.
[0060] Fig.17 These are SEM images of the pure silicon electrode before and after 5 cycles (top / side view).
[0061] Fig.18 These are the SEM images (top / side views) of the Si@LaF3-20 electrode before and after 5 cycles.
[0062] Fig.19 These are low-magnification TEM, HRTEM, and EDX images of pure silicon electrodes after cycling.
[0063] Fig. 20 These are the low-magnification TEM, HRTEM, and EDX images of the Si@LaF3-20 electrode after cycling.
[0064] Fig.21 Pure silicon, Si@LaF3 and Si@LiF electrodes at 0.3A·g -1 Comparison of cycling performance under different current densities.
[0065] Fig. 22 , (a) is the scanning rate of Si@LaF3 at 0.1mV·s -1 (b) is the 1st to 5th CV curves of pure silicon electrode at a scan rate of 0.1 mV·s -1(a) is the 1st to 5th CV curves; (c) is the GCD curve of Si@LaF3; (d) is the GCD curve of pure silicon electrode; (e) is the Nyquist plot of Si@LaF3 and pure silicon electrode before cycling; (f) is the Nyquist plot after cycling.
[0066] Fig.23 , (a) is the equivalent circuit diagram of Si@LaF3 electrode before cycling; (b) is the equivalent circuit diagram after cycling.
[0067] Fig.24 This is the cycling performance diagram of the Si@LaF3||LFP full battery at a current density of 0.35C.
[0068] Fig.25 This is the rate performance diagram of the Si@LaF3||LFP full battery.
[0069] Fig.26 This is the GCD curve of Si@LaF3||LFP full battery at a current density of 0.35C.
[0070] Fig. 27 This is the Nyquist plot of Si@LaF3||LFP full battery before and after cycling.
[0071] Fig.28 This is a comparison chart of the cycle performance of pure graphite electrode, Si / graphite mixed electrode and Si@LaF3 / graphite mixed electrode.
[0072] Fig.29 This is a comparison chart of the cycle performance of Si@LaF3 / graphite mixed electrode and pure graphite electrode in all-solid-state batteries. DETAILED DESCRIPTION
[0073] In order to make the purpose, technical solutions and advantages of the embodiments of the present disclosure clearer, the technical solutions in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present disclosure. Therefore, the following detailed description of the embodiments of the present disclosure provided in the drawings is not intended to limit the scope of the present disclosure for protection, but merely represents the selected embodiments of the present disclosure. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present disclosure.
[0074] Example 1
[0075] The present disclosure provides a method for preparing a Si@LaF3 composite material.
[0076] The method specifically comprises:
[0077] Commercial nano-silicon with a particle size of 100 nm (purchased from Shanghai Xiangtian Nanomaterials Co., Ltd.) was used without any treatment.
[0078] The nano-silicon and commercially available lanthanum fluoride LaF3 powder were ball-milled at a speed of 400 rpm for 4 hours in an argon environment to prepare a Si@LaF3 composite material.
[0079] The particle size of nano-silicon and lanthanum fluoride powders will affect the properties of the prepared composite materials.
[0080] Since nano-silicon will have a huge volume expansion (~400%) during the lithiation process, the disclosed embodiment selects nano-silicon with a particle size of no more than 150 nm to reduce the impact of the volume expansion of nano-silicon during the lithiation process.
[0081] Si@LaF3 composite materials samples were prepared using nano-silicon and lanthanum fluoride powders in different mass ratios.
[0082] The mass ratios of nano-silicon and lanthanum fluoride powder are 9:1, 4:1 and 7:3 respectively. The prepared samples are respectively recorded as Si@LaF3-10, Si@LaF3-20 and Si@LaF3-30.
[0083] In the embodiments of the present disclosure, a scanning electron microscope (SEM) (Zeiss, EVO 18, Germany) and a transmission electron microscope (TEM) (FEI, Talos 200S, USA) were used to characterize the morphology, lattice structure and SEI formation of the samples.
[0084] Firstly, the microstructures of nano-silicon samples, Si@LaF3-20 samples and Si@LaF3-30 samples used as preparation raw materials were observed by SEM.
[0085] The SEM characterization results of the nano-silicon sample are as follows Figure 1 shown.
[0086] Figure 1 It shows that nano-silicon particles with a diameter of 100nm are aggregated and connected in series, and the whole is in a chain or branched shape.
[0087] The SEM characterization results of Si@LaF3-20 samples are shown in Figure 2 The Si@LaF3-20 sample is prepared by ball milling nano-silicon and an appropriate amount of lanthanum fluoride.
[0088] Figure 2 It shows that there is no significant change in the size of nano-silicon particles, but the particle dispersion is significantly improved.
[0089] The corresponding energy dispersive X-ray spectroscopy (EDX) analysis results of Si@LaF3-20 samples are shown in Figure 3 shown.
[0090] Figure 3 It shows that silicon Si, lanthanum La, and fluorine F elements are evenly distributed in the Si@LaF3-20 sample, and there are almost no lanthanum fluoride agglomerates, indicating that an appropriate amount of lanthanum fluoride can be evenly dispersed around nano-silicon particles after ball milling.
[0091] The SEM characterization results of Si@LaF3-30 samples are shown in Figure 4 shown.
[0092] Figure 4 It is clearly observed that in the Si@LaF3-30 sample, small fragments are formed by self-aggregation of lanthanum fluoride particles due to excessive addition of lanthanum fluoride in the raw materials.
[0093] Furthermore, the microstructures of the nano-silicon sample, Si@LaF3-20 sample and Si@LaF3-30 sample were characterized in detail using HRTEM and EDX.
[0094] The TEM characterization results of the nano-silicon sample are as follows: Figure 5 shown.
[0095] Figure 5 The surface of pure nano-silicon with branched shape is smooth and mainly composed of polycrystalline silicon.
[0096] TEM characterization results of Si@LaF3-20 samples are shown in Figure 6-8 shown.
[0097] Compared with the nano-silicon sample, dispersed particles of 100 nm and 30 nm were observed in the Si@LaF3-20 sample, and their lattice spacings were 0.31 nm and 0.357 nm, respectively, corresponding to the (111) crystal plane of nano-silicon and the (111) crystal plane of lanthanum fluoride crystals.
[0098] In particular, a rough amorphous layer appeared on the surface of the nano-Si particles.
[0099] As shown in Table 1, since nano-silicon has a higher Young's modulus than lanthanum fluoride, during high-energy ball milling, lanthanum fluoride particles are preferentially broken, or dispersed around nano-silicon particles, or adhered to the surface of nano-silicon particles to form a lanthanum fluoride amorphous layer coating.
[0100] Table 1. Young's modulus data of LaF3, Si and LiF
[0101]
[0102] The corresponding EDX analysis results of Si@LaF3-20 samples are shown in Fig. 9 shown.
[0103] According to the EDX element distribution under TEM, although a small amount of unbroken lanthanum fluoride particles are dispersed between the nano-silicon particles, there are also obvious signals of F and La elements on the surface of the nano-silicon particles, which further proves the existence of an amorphous phase layer of lanthanum fluoride on the surface of the nano-silicon particles.
[0104] In the Si@LaF3 composite material provided in the embodiments of the present disclosure, the sustained release effect of a small amount of lanthanum fluoride particles and the function of the lanthanum fluoride thin layer on the surface of the nano-silicon particles are very important for improving the lithium insertion and extraction performance of the electrode material.
[0105] The embodiments of the present disclosure use an X-ray diffractometer (XRD) (Paasch, The Netherlands) to obtain the phase structure characterization of the sample.
[0106] X-ray diffraction (XRD) was used to characterize the composition and crystal characteristics of Si@LaF3-10 sample, Si@LaF3-20 sample and Si@LaF3-30 sample.
[0107] like Fig.10 As shown, the Si@LaF3 composite reveals characteristic diffraction peaks at approximately 28.4°, 47.36°, and 56.1° that are highly consistent with the cubic phase of Si (PDF#88-0018), corresponding to the (111), (220), and (311) planes of crystalline Si.
[0108] The characteristic diffraction peaks of the Si@LaF3 composite at about 27.6°, 43.6°, and 44.7° match those of LaF3 crystal very well and are also very consistent with its PDF card (PDF#32-0483).
[0109] When the amount of lanthanum fluoride added is appropriate or below, most of the lanthanum fluoride crystals are broken during the ball milling process and adhere to the surface of nano-silicon to form an amorphous lanthanum fluoride coating layer, and the characteristic peaks of the Si@LaF3 composite material are mainly Si.
[0110] like Fig.11 As shown, when the addition amount of lanthanum fluoride is excessively increased, even after ball milling, the characteristic peak of lanthanum fluoride is still stronger than the characteristic peak of nano-silicon, indicating the presence of excessive lanthanum fluoride crystal fragments.
[0111] In addition, no new XRD peaks appeared in the XRD patterns of the Si@LaF3 composites, indicating that no new crystalline phase was generated during the ball milling process.
[0112] The present embodiment uses a monochromatic Al kα radiation source (1486.6 eV) to characterize the surface chemical state by X-ray photoelectron spectroscopy (XPS) on a PHI 5000 Versaprobe II instrument, and corrects the binding energy of C1s at 284.8 eV.
[0113] The chemical states of Si, F and La in the Si@LaF3 composite were further characterized by X-ray photoelectron spectroscopy (XPS). The XPS spectrum of Si 2p is shown in Figure 2. Fig.12 As shown in Figure 2, the binding energy peak at 98.6 eV is attributed to the Si-Si bond. Meanwhile, due to the inevitable oxidation of nano-Si exposed to air, the peaks near 102.5 and 103.35 eV are attributed to Si-OC and SiO, respectively. x (0<x≤2).
[0114] like Fig.12 As shown in Figure 1, even though the amount of addition is much less than that of silicon, the LaF3 signal present on the surface is clearly collected by the XPS test. The strong peak centered at 683.3 eV in the XPS spectrum of F1s is attributed to LaF3, La 3d 5 / 2 The XPS spectrum also shows two strong spin-orbit peaks corresponding to LaF3, located at about 835.2 and 839.3 eV respectively.
[0115] The above results show that the appropriately added lanthanum fluoride is mainly distributed on the surface of silicon particles after high-energy ball milling, and a small amount is dispersed between the silicon particles, forming a Si@LaF3 composite material.
[0116] Example 2
[0117] Preparation of liquid half-cell:
[0118] The nano-silicon, Si@LaF3-10, Si@LaF3-20 and Si@LaF3-30 composite materials are respectively used as active materials.
[0119] The active material, carbon black (Super-P), styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) binder are mixed in a mass ratio of 7:1:1:1 to form a slurry, wherein the SBR and CMC binders are respectively configured as 1% solutions.
[0120] The slurry was coated on copper foil. The coated copper foil was placed in a vacuum oven at 80 °C and dried overnight, then cut into pieces with a diameter of 12 mm and an active mass loading of 0.8-1.0 mg cm -2 working electrode.
[0121] Lithium metal was used as the counter electrode and the button cell was assembled in a glove box (Mikrouna) filled with argon gas, wherein the oxygen and water contents in the glove box were both less than 0.1 ppm.
[0122] The prepared working electrode, lithium metal counter electrode, porous polypropylene separator (Celgard) and electrolyte were assembled into a CR2025-typed button half-cell. The electrolyte was a 1M LiPF6 solution and the solvent was a solution of ethylene carbonate (EC), diethyl carbonate (DEC) and dimethyl carbonate (DMC) mixed in a mass ratio of 1:1:1.
[0123] The assembled liquid half-cell samples were aged for 12 h and then tested at room temperature.
[0124] The embodiment of the present invention is 0.1-2A·g -1 Current density, 0.01-1.5V (vs.Li / Li + ) voltage range, the rate performance and cycle performance of the battery samples were tested on a NEWARE battery tester (Shenzhen, China).
[0125] Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were performed on an electrochemical workstation (Chenhua, CHI660E). -1 Cyclic voltammetry was performed at a scan rate of 1.1 kHz. Electrochemical impedance spectroscopy was performed in a frequency range of 0.01-100 KHz.
[0126] All electrochemical measurements of the liquid batteries were performed at room temperature.
[0127] In a half-cell system with lithium metal as the counter electrode, the + ) voltage window, the electrochemical performance of the Si@LaF3 composite material with nano-silicon and different lanthanum fluoride addition ratios was evaluated.
[0128] like Fig.13 As shown in the figure, compared with pure silicon electrode, Si@LaF3 composite electrode has better electrochemical performance. In particular, the performance of Si@LaF3-20 electrode is greatly improved, and its initial charge and discharge capacities are 2163.7 and 2984.1 mAh·g, respectively. -1 , corresponding to an initial Coulombic efficiency (ICE) of 72.5%.
[0129] Each sample was subjected to 0.1A g -1 After 5 cycles of activation at a current density of 0.3 A·g -1 The cycling performance was compared at a current density of 2295.9 mAh g-1 The initial capacity of the sample was 567 mAh g after 200 cycles. -1 In comparison, the specific capacity of Si@LaF3-20 electrode after 200 cycles is about 1230.2 mAh g -1 , the capacity retention rate is 66.9%, showing excellent reversible specific capacity.
[0130] The rate performance tests were carried out at different current densities to verify the enhanced rate performance of Si@LaF3 composite materials. Fig.14 As shown, with 0.1, 0.2, 0.5, 1 and 2A·g -1 The Si@LaF3-20 electrode provided 1947.5, 1695.7, 1396.8, 1072.6, and 589.8 mAh·g -1 High reversible capacity. In particular, when the current density is reduced to 0.1A·g -1 When -1 , indicating that it has excellent stability during high current density charge and discharge. In contrast, the capacity of pure silicon electrode and other Si@LaF3 composite electrodes dropped sharply, and the pure silicon electrode was -1 Almost all of its capacity is lost at a current density of 1.5 %, and the capacity recovery is relatively poor as the current gradually decreases.
[0131] The excellent cycling stability of Si@LaF3-20 electrode can be demonstrated by 1A·g -1 The long-term cycle test under current density further verified. Fig.15 As shown in Figure 2, the pure silicon electrode quickly loses all its capacity, and the Si@LaF3-10 and Si@LaF3-30 electrodes only have 101.8 and 103 mAh·g after 500 cycles. -1 However, the specific capacity of Si@LaF3-20 electrode is 1A·g -1 After 500 cycles, the current density remains at 338.5 mAh g -1 High reversible capacity and high coulombic efficiency.
[0132] The constant current intermittent titration technique (GITT) was used to further evaluate the -1 Diffusion coefficient of lithium ions in pure silicon and Si@LaF3-20 electrodes at current density of .
[0133] like Fig.16 As shown in Figure 2, the diffusion of lithium ions in pure silicon and Si@LaF3-20 electrodes is significantly different. For Si@LaF3-20 electrodes, the lithium ion diffusion coefficient (D Li+) always maintains a constant high value of ≈10 during the alloying stage -10 cm 2 ·s -1 During the whole dealloying process, the D Li+ It is also relatively stable, with values as high as ≈10 -11 cm 2 ·s -1 , which is higher than that of pure silicon electrode. Therefore, the interaction between the appropriate amount of lanthanum fluoride dispersed particles and the coating layer leads to a significant improvement in the lithium insertion and extraction kinetics and long-term cycle stability of the Si@LaF3 composite material.
[0134] In view of the excellent cycle performance and rate performance of the Si@LaF3-20 electrode, the Si@LaF3-20 electrode is used as the research object in the subsequent embodiments and is named Si@LaF3 for convenience.
[0135] Example 3
[0136] In order to explore the excellent cycling stability of Si@LaF3 electrode, the morphological evolution of pure silicon and Si@LaF3 electrodes before and after cycling was characterized by SEM.
[0137] Before characterizing the cycled samples, the disassembled cycled electrode sheets were rinsed with dimethyl carbonate in a glove box filled with argon. After the solvent evaporated, the electrode morphology was characterized by ex situ SEM. The powder was scraped from the dried electrode sheet, ultrasonically dispersed in an ethanol solution, and loaded onto a copper grid carbon film for ex situ TEM characterization.
[0138] like Fig.17 As shown in the figure, after 5 cycles, the thickness of the pure silicon electrode increased from 23μm to 142μm, the expansion rate was 517%, and the entire surface of the pure silicon electrode was covered with cracks. This structure shows that the SEI formed at the silicon / electrolyte interface can neither prevent the occurrence of serious side reactions nor effectively suppress the huge volume changes, which ultimately aggravates the decomposition of the electrolyte on the newly exposed silicon surface. At the same time, the separation of active silicon and the current collector was observed, which will also lead to reduced electrical contact between particles and increased charge transfer resistance.
[0139] On the contrary, Fig.18As shown, a smooth surface is displayed on the Si@LaF3 electrode, which is due to the effective passivation interface of the LiF-rich SEI formed rapidly in situ by the lanthanum fluoride modification layer, which reduces the occurrence of side reactions. In addition, the inhibition of the volume expansion of nano-silicon shows that the inorganic SEI based on the conversion of the lanthanum fluoride modification layer has the ability to withstand large volume expansion. After 5 cycles of the Si@LaF3 electrode, the thickness of the electrode only increased from 23μm to 31μm, and the expansion rate was only 34.7%. No obvious large-scale cracks were found on the electrode surface, and the active material and the current collector were still in close contact, which also helps to shorten the ion transmission distance, accelerate the transmission of lithium ions and fast charge and discharge.
[0140] Fig.19 TEM image of pure silicon electrode after 100 cycles.
[0141] It is observed in the figure that pure nano-silicon particles form amorphous silicon agglomerates after cycling due to repeated volume expansion and electrochemical sintering. The nano-silicon structure is severely damaged, the particle morphology has become nanoporous, the SEI layer on the periphery is thicker and looser, and the F element signal distribution is not concentrated.
[0142] Fig. 20 TEM image of Si@LaF3 electrode after 100 cycles.
[0143] It is observed in the figure that the structure of the nano-silicon particles remains intact, and a uniform and dense SEI layer of about 18nm thick is formed on its surface. EDX can also observe that the Si signal is located in the core of the Si@LaF3 particles, and the structure remains intact, indicating that the rapidly formed stable fluorine-rich SEI layer effectively inhibits the volume expansion and destruction of the nano-silicon particles. The F signal and La signal are dispersed in the nano-silicon particles. The lanthanum metal can adsorb electrolyte anion groups, promote the free movement of lithium ions, realize the selective high-flux transport of lithium ions toward the nano-silicon particles, inhibit radical side reactions, and excessive generation of SEI.
[0144] In addition, if Fig. 20 As shown in the figure, the presence of some dispersed lanthanum fluoride particles indicates that they are passivated after the formation of LiF on their surface, and will not consume excessive lithium ions. These appropriate amounts of rigid lanthanum fluoride crystals dispersed in the nano-silicon negative electrode help to inhibit the sintering and agglomeration of nano-silicon particles, thereby maintaining the good electrochemical performance of the nano-silicon negative electrode.
[0145] Fig.21 Comparing the cycling performance of Si@LiF electrodes under the same preparation and testing conditions, the ball-milled LiF artificial SEI has little effect on the improvement of the performance of the nano-silicon negative electrode. This further confirms that the stability of the Si@LaF3 electrode is caused by the synergistic effect of the appropriate amount of dispersed lanthanum fluoride, the in-situ formed LiF passivation layer, and the La particles.
[0146] To understand the good lithium insertion and delithiation kinetics of Si@LaF3 composites, Si@LaF3 and pure silicon electrodes were subjected to a voltage range of 0.01–1.5 V at a rate of 0.1 mV·s -1 The initial five CV curves were obtained at a scan rate of Fig. 22 As shown in a and b.
[0147] In the first scan, two reduction peaks appear at about 0.01 V and 0.15 V, which are due to the lithiation of crystalline silicon to form Li-Si alloy. During the anodic scan, the anodic peaks at about 0.35 and 0.54 V correspond to the anodic reduction from Li x Si or Li 15 Si4 is converted to Si. In the second cycle, the cathode peak at about 0.01V weakened, while a new cathode peak appeared around 0.15V, corresponding to the irreversible phase transition from crystalline silicon to amorphous silicon in the composite material. In addition, compared with the pure silicon electrode, the characteristic peak intensity of the cathode and anode of the Si@LaF3 electrode increased with the increase of cycles, which is attributed to the La particles generated by the reaction of lanthanum fluoride with lithium ions, which can adsorb anionic groups in the electrolyte and promote the free migration of lithium ions in the silicon electrode, so that more active materials are activated to react with lithium metal, enhancing the reversibility of the electrode and the fast electrochemical reaction kinetics.
[0148] Fig. 22 c, d are Si@LaF3 and pure silicon electrodes at 0.1 A·g -1 Galvanostatic charge / discharge (GCD) curves of the first three cycles at the current density. The platform voltage observed in the GCD curve is consistent with the peak voltage in the CV curve.
[0149] Electrochemical impedance spectroscopy (EIS) revealed the rapid reaction kinetics in the Si@LaF3 electrode and further clarified the effect of lanthanum fluoride on the electrochemical properties of nano-silicon.
[0150] like Fig. 22 As shown in e and f, all EIS spectra are composed of high-frequency semicircles and low-frequency straight lines, which correspond to the charge transfer resistance (Rct) and Warburg resistance (Wo), respectively. Based on the above content, the equivalent circuit diagram is as follows Fig.23 As shown, the available impedance parameters are recorded in Table 2.
[0151] Table 2. Impedance fitting values of pure silicon and Si@LaF3 electrodes before and after cycling
[0152]
[0153] Before cycling, the introduction of lanthanum fluoride promoted the interfacial charge transfer between the Si@LaF3 electrode and the electrolyte, significantly reducing the interfacial impedance. After cycling, the Si@LaF3 electrode showed the smallest impedance, indicating that the in-situ formed fluorine-rich SEI and La particles gradually optimized the interfacial structure of the silicon electrode during repeated charge and discharge, thereby achieving fast and stable charge transfer.
[0154] Example 4
[0155] To further evaluate the electrochemical performance of Si@LaF3, a Si@LaF3||LFP full cell composed of commercial LiFePO4 (LFP) was also fabricated.
[0156] For the Si@LaF3||LFP full cell, LFP was used as the cathode. The Si@LaF3 electrode was cycled for 5 cycles in the half-cell and then assembled in the full cell. The capacity ratio of the anode to the cathode (N / P) was adjusted to about 1.1.
[0157] like Fig.24 As shown, the Si@LaF3||LFP full battery can provide 147.6mAh·g at a current density of 0.35C. -1 The initial coulombic efficiency is 99.1%, and it still maintains 125.1 mAh g after 200 cycles. -1 The discharge capacity of the battery was 84.7%, with a capacity retention rate of 84.7%, showing good cycle stability.
[0158] In addition, if Fig.25 As shown in Figure 2, the full cell also exhibits excellent rate capability, providing 106.8 mAh g at a current density of 0.6 C. -1 The reversible capacity can provide 70.3 mAh g at 1.2C current density. -1 The reversible capacity fully demonstrates the superior rate capability of the full battery.
[0159] The GCD curve of the Si@LaF3||LFP full battery in the fully charged state is as follows Fig.26 As shown in Figure 1, the capacity decay is caused by the irreversible phase change of the positive and negative electrodes.
[0160] like Fig. 27 As shown, according to the electrochemical impedance spectroscopy (EIS), the impedance of the full cell increases significantly after 200 cycles, which is related to the slow capacity decay of the full cell.
[0161] Overall, the Si@LaF3||LFP full cell exhibits high capacity and good cycling stability, which supports its application as a potential anode in electrical devices.
[0162] Example 5
[0163] In order to explore the commercial potential of Si@LaF3 materials in high energy density lithium-ion batteries, Si@LaF3 / graphite hybrid electrodes were prepared by adding Si@LaF3-20 composites as active materials to commercial graphite. For comparison, Si / graphite hybrid electrodes and pure graphite electrodes were also prepared.
[0164] In the Si@LaF3 / graphite mixed electrode, the amount of Si@LaF3-20 composite material is 15wt% of the total amount of commercial graphite and Si@LaF3-20 composite material. In the Si / graphite mixed electrode, the amount of silicon material is 15wt% of the total amount of commercial graphite and silicon material.
[0165] All prepared electrodes have similar active mass loading (~1.0 mg cm -2 ).
[0166] At 0.1A·g -1 At a current density of , the constant current charge / discharge performance of Si@LaF3 / graphite mixed electrode, Si / graphite mixed electrode and pure graphite electrode is shown in Fig.28 shown.
[0167] Si@LaF3 / graphite hybrid electrode at 0.1A·g -1 After 300 cycles, the battery capacity is 518.3 mAh g -1 In contrast, the Si / graphite hybrid electrode exhibited poor cycling stability, with its capacity decaying to 271.2 mAh g after 300 cycles. -1 The capacity retention rate is 42.8%, which is much lower than the 518.3 mAh g of Si@LaF3 / graphite hybrid electrode. -1 , even lower than the 332.8mAh·g of pure graphite electrode -1 .
[0168] Preparation of polyethylene oxide (PEO)@LLZTO composite solid electrolyte membrane:
[0169] 0.917g PEO powder, 0.332g lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 0.046g LLZTO nanoparticles were dissolved in acetonitrile and stirred at room temperature for 24h. The slurry was then poured into a clean Teflon mold and dried at 50℃ under vacuum for 12h to obtain a PEO@LLZTO solid composite electrolyte membrane. The thickness of the PEO@LLZTO solid composite electrolyte membrane is ~200μm.
[0170] The PEO@LLZTO solid electrolyte membrane was used to replace the membrane and electrolyte of the liquid half-cell in Example 2 to prepare an all-solid-state half-cell.
[0171] For all-solid-state batteries, the cycle performance test was carried out in a constant temperature box at 60°C.
[0172] Si@LaF3 / graphite hybrid electrodes also have excellent electrochemical performance in all-solid-state batteries.
[0173] like Fig.29 As shown, at a current density of 0.1 A g -1 Under the condition of low temperature, Si@LaF3 / graphite hybrid electrode showed 638mAh·g -1 The reversible specific capacity and initial Coulomb efficiency of 99.2% indicate that the Si@LaF3 / graphite hybrid electrode also achieves relatively stable cycle performance in all-solid-state batteries. After 100 cycles, the capacity is still 491 mAh g -1 .
[0174] In sharp contrast, in all-solid-state batteries, pure graphite electrodes have a current density of 0.1 A g -1 After 20 cycles, the battery capacity is only 295 mAh g -1 capacity.
[0175] The embodiment of the present invention prepares a low-cost Si@LaF3 nanocomposite material by a simple one-step ball milling method. The rigid LaF3 particles form a thin layer of lanthanum fluoride on the surface of the nano-silicon particles during the high-energy ball milling process, and the excess LaF3 particles are dispersed in the silicon electrode. When lithium ions are embedded, the thin layer of lanthanum fluoride preferentially induces the nano-silicon surface to form a LiF-rich SEI layer with ionic conductivity and mechanical flexibility, which reduces the occurrence of interfacial side reactions through effective passivation. At the same time, the lanthanum particles generated by the reaction of lanthanum fluoride and lithium ions can adsorb the anionic groups of the electrolyte, promote the free migration of lithium ions in the silicon electrode, and enhance the reaction kinetics of the electrode. The LaF3 particles dispersed in the silicon electrode in an appropriate amount can alleviate the electrochemical sintering of the nano-silicon particles and inhibit the local excessive volume expansion stress and damage of the silicon electrode. Therefore, compared with pure nano-silicon particles, this Si@LaF3 particle that is easy to scale up has a lithium storage capacity with both high specific capacity and cycle stability. In particular, the Si@LaF3||LFP full battery maintains 125.1mAh·g after 200 cycles at 0.35C. -1 In addition, thanks to the optimized lithium ion conduction and limited interfacial side reactions, the all-solid-state lithium battery based on Si@LaF3 / graphite hybrid electrode has a high specific capacity of 0.1A·g -1 After 100 cycles, the capacity remains at 491 mAh g -1 Specific capacity.
[0176] The present work provides new insights into the commercialization of silicon-based anodes for next-generation lithium-ion batteries and the application of all-solid-state batteries.
[0177] The above description is only a preferred embodiment of the present disclosure and is not intended to limit the present disclosure. For those skilled in the art, the present disclosure may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present disclosure shall be included in the protection scope of the present disclosure.
Claims
1. A method for preparing a Si@LaF3 composite material, characterized in that: The method comprises: ball-milling nano-silicon and lanthanum fluoride powder in an inert environment to obtain the Si@LaF3 composite material, wherein the mass proportion of the lanthanum fluoride powder is 10%-30% based on the total amount of the nano-silicon and the lanthanum fluoride powder.
2. The preparation method according to claim 1, characterized in that Based on the total amount of the nano-silicon and the lanthanum fluoride powder, the mass ratio of the lanthanum fluoride powder is 15%-25%.
3. The preparation method according to claim 1 or 2, characterized in that: The particle size of the nano silicon powder is no more than 150 nm.
4. A Si@LaF3 composite material, characterized in that: The Si@LaF3 composite material comprises nano-silicon particles and a lanthanum fluoride amorphous coating layer on the surface of the nano-silicon particles. The Si@LaF3 composite material also comprises lanthanum fluoride particles dispersed between the nano-silicon particles.
5. Use of the Si@LaF3 composite material prepared by the method according to any one of claims 1 to 3 in anode materials for lithium-ion batteries, or use of the Si@LaF3 composite material according to claim 4 in anode materials for lithium-ion batteries.
6. The use according to claim 5, characterized in that The lithium ion battery is a half-cell or a full-cell.
7. The use according to claim 5, characterized in that The lithium ion battery is a liquid lithium ion battery or an all-solid lithium ion battery.
8. The use according to claim 5, characterized in that The anode material includes graphite.
9. A lithium ion battery anode material, characterized in that: The anode material comprises the Si@LaF3 composite material prepared by the method according to any one of claims 1 to 3 and graphite, or the anode material comprises the Si@LaF3 composite material according to claim 4 and graphite.
10. An anode material according to claim 9, characterized in that In the anode material, the mass proportion of the Si@LaF3 composite material is 10%-20%.